(untitled) - Hsu, Immanuel C. Y (New York, 1970)
This book consists of the following six parts: The persistence of traditional institutions 1600-1800, Foreign aggression and domestic rebellions 1800-1864, Self-strengthening in an age of accelerated foreign imperialism 1861-95, Reform and revolution 1898-1912, Ideological awakeing and the war of resistance 1917-45, The rise of the Chinese people's republic.
Keywords: History,History; Qing dynasty; 1644-1912,20th century; China,China